The long road to normalcy: Where Russia now stands - Vladimir Popov (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
The goal of this study is to reveal the long-term trajectory of Russian economic development and to make predictions for the future. The study starts with a much discussed question: why Russia did worse economically during transition than most other countries in Europe and Asia? It is argued that it was partly caused by objective circumstances before transition (distortions in industrial structure and in trade patterns accumulated during the era of central planning), but mostly by the weakening of the institutional capacity of the state during transition.
Keywords: O11; O57; P27; P52; 330; economic transition; institutional trajectories; Russia; China; Übergangswirtschaft; Institutionalismus; Wirtschaftliche Anpassung; Systemvergleich; China; Russland